Diversity of bacterial community in Jerusalem artichoke (Helianthus tuberosus L.) during storage is associated with the genotype and carbohydrates - Du, Guolian; Sun, Zhu; Bao, Shanhua; Zhong, Qiwen; Yang, Shipeng (Frontiers in Microbiology, 2022)
Jerusalem artichoke (JA) is a fructan-accumulating crop that has gained popularity in recent years. The objective of the present study was to determine the dynamics of the JA-microbiome during storage. The microbial population on the surface of the JA tuber was determined by next-generation sequencing of 16S rRNA amplicons. Subsequently, the changes in carbohydrate and degree polymerization of Fructan in tubers during storage were measured. Among different genotypes of JA varieties, intergeneric differences were observed in the diversity and abundance of bacterial communities distributed on the surface of tubers. Additionally, bacterial diversity was significantly higher in storage-tolerant varieties relative to the storage-intolerant varieties. Redundancy analysis (RDA) and the correlation matrix indicated a relationship between changes in the carbohydrate and microbial community succession during tuber storage. Tuber decay rate is correlated positively with degree polymerization of Fructan. Moreover, Dysgonomonas and Acinetobacter in perishable varieties are correlated significantly with the decay rate. Therefore, the bacteria associated with the decay rate may be involved in the degradation of the degree polymerization of Fructan. Furthermore, Serratia showed a significant positive correlation with inulin during storage but a negative correlation with the decay rate, suggesting its antagonistic role against pathogenic bacteria on the surface of JA tubers. However, the above correlation was not observed in the storage-tolerant varieties. Functional annotation analysis revealed that storage-tolerant JA varieties maintain tuber quality through enrichment of biocontrol bacteria, including Flavobacterium, Sphingobacterium, and Staphylococcus to resist pathogens. These results suggested that crop genotype and the structural composition of carbohydrates may result in differential selective enrichment effects of microbial communities on the surface of JA varieties. In this study, the relationship between microbial community succession and changes in tuber carbohydrates during JA storage was revealed for the first time through the combination of high-throughput sequencing, HPLC, and HPIC. Overall, the findings of this study are expected to provide new insights into the dynamics of microbial-crop interactions during storage.